Effect of COVID-19 pandemic on provision of sexual and reproductive health services in primary health facilities in Nigeria: a cross-sectional study - Babatunde Adelekan; Erika Goldson; Zubaida Abubakar; Ulla Mueller; Audu Alayande; Tellson Ojogun; Lorretta Ntoimo; Bukky Williams; Ibrahim Muhammed; Friday Okonofua (BMC, 2021)
Plain language summary The onset of COVID-19 has raised concerns that it may compromise women's access to sexual and reproductive health and rights. Although data are still emerging, some reports indicate reduced access to sexual and reproductive health services, largely due to disruptions in the demand and supply of contraceptive commodities, the diversion of staff and resources to other clinical services, and clinic closures. While these concerns have similarly been broached for Nigeria, there has been no systematic documentation of the extent of the disruptions of reproductive health services caused by COVID-19 and its effects on the provision and utilization of related services in the country This study was a cross-sectional facility-based survey conducted in 10 states, 30 Local Government Areas and 302 primary health centres in Nigeria. The objective of the study was to explore through key informant interviews with service providers in the health centres, the effects of the COVID-19 pandemic on demand and supply of sexual and reproductive health services. Field assistants administered a semi-structured interview guide to the heads of the health centres that elicited information on availability and use of the health centres before, during and after the lock-downs associated with the pandemic. The results indicate that a large proportion of the health centres opened for the provision of essential sexual and reproductive health services during the COVID-19 pandemic lockdown. However, fewer clients used the services due to difficulties in travel because of the lockdowns, stock-outs in the health centres, and the fear that they may contract the virus if they leave their houses to the health centres. Although the health centres reported some cases of COVID-19, there was limited provision for personal protective equipment to motivate the health workers to optimize services for clients. From this study, we conclude that efforts should be made to identify innovations for addressing these challenges to enable the continued provision of sexual and reproductive health services by health centres despite the COVID-19 pandemic in Nigeria's health centres.